2016
DOI: 10.1074/jbc.m116.714063
|View full text |Cite
|
Sign up to set email alerts
|

Iron- and Quorum-sensing Signals Converge on Small Quorum-regulatory RNAs for Coordinated Regulation of Virulence Factors in Vibrio vulnificus

Abstract: Vibrio vulnificus is a marine bacterium that causes human infections resulting in high mortality. This pathogen harbors five quorum-regulatory RNAs (Qrr1-5) that affect the expression of pathogenicity genes by modulating the expression of the master regulator SmcR. The qrr genes are activated by phosphorylated LuxO to different degrees; qrr2 is strongly activated; qrr3 and qrr5 are moderately activated, and qrr1 and qrr4 are marginally activated and are the only two that do not respond to cell density-dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
38
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 71 publications
0
38
0
2
Order By: Relevance
“…smcR mutants show attenuated cytotoxicity compared to the wild type (Lee et al, 2007). Wen et al (2016) showed that Qrr sRNAs in V. vulnificus are regulated via LuxO and modulate the expression of virulence factors via SmcR. Interestingly, the authors also showed that Qrr sRNAs are responsive to iron concentration, and that iron and QS converge on Qrrs to control the expression of virulence factors (Wen et al, 2016) ( Figure 2 ).…”
Section: Srnas Implicated In Processes Related To Virulence In Human mentioning
confidence: 99%
See 3 more Smart Citations
“…smcR mutants show attenuated cytotoxicity compared to the wild type (Lee et al, 2007). Wen et al (2016) showed that Qrr sRNAs in V. vulnificus are regulated via LuxO and modulate the expression of virulence factors via SmcR. Interestingly, the authors also showed that Qrr sRNAs are responsive to iron concentration, and that iron and QS converge on Qrrs to control the expression of virulence factors (Wen et al, 2016) ( Figure 2 ).…”
Section: Srnas Implicated In Processes Related To Virulence In Human mentioning
confidence: 99%
“…Small non-coding RNAs can modulate the expression of genes associated with survival and virulence by pairing with untranslated regions of genes in response to cell density, through the QS pathway (Wen et al, 2016). QS is a process of cell communication by which a bacterial population expresses a set of genes in a coordinated way in response to the cell density in the population (Hammer and Bassler, 2007; Shao and Bassler, 2012, 2014; Van Kessel et al, 2015) through the production, release, detection and response to extracellular signal molecules called autoinducers (Tu and Bassler, 2007; Rutherford et al, 2011).…”
Section: Srnas Implicated In Processes Related To Virulence In Human mentioning
confidence: 99%
See 2 more Smart Citations
“…The autoinducer-receptor systems in V. parahaemolyticus are likely similar to those in V. harveyi, based on phylogenetic analyses and signaling assays (10,14,16,42), whereas only the LuxPQ system that detects AI-2 has been identified in V. vulnificus (40). The number of Qrrs in different Vibrio species varies from one to five among vibrios, and they act either additively or redundantly (15,45,(52)(53)(54)(55)(56). Further, the Qrr regulon in V. harveyi (ϳ20 genes) does not appear to include the type VI secretion genes, which are regulated by the Qrrs in V. cholerae (50,57).…”
mentioning
confidence: 99%